The home stroke rehabilitation and monitoring system trial: a randomized controlled trial. Issue 1 (24th December 2012) - Linder, Susan M.; Rosenfeldt, Anson B.; Reiss, Aimee; Buchanan, Sharon; Sahu, Komal; Bay, Curtis R.; Wolf, Steven L.; Alberts, Jay L.
Abstract : Rationale: Because many individuals poststroke lack access to the quality and intensity of rehabilitation to improve upper extremity motor function, a home‐based robotic‐assisted upper extremity rehabilitation device is being paired with an individualized home exercise program. Aims/Hypothesis: The primary aim of this project is to determine the effectiveness of robotic‐assisted home therapy compared with a home exercise program on upper extremity motor recovery and health‐related quality of life for stroke survivors in rural and underserved locations. The secondary aim is to explore whether initial degree of motor function of the upper limb may be a factor in predicting the extent to which patients with stroke may be responsive to a home therapy approach. We hypothesize that the home exercise program intervention, when enhanced with robotic‐assisted therapy, will result in significantly better outcomes in motor function and quality of life. Design: A total of 96 participants within six‐months of a single, unilateral ischemic, or hemorrhagic stroke will be recruited in this prospective, single‐blind, multisite randomized clinical trial. Study Outcomes: The primary outcome is the change in upper extremity function using the Action Research Arm Test. Secondary outcomes include changes in: upper extremity function (Wolf Motor Function Test), upper extremity impairment (upper extremity portion of the Fugl‐Meyer Test), self‐reported quality of life (Stroke Impact Scale), and affect (Centers for Epidemiologic Studies Depression Scale). Discussion: Similar or greater improvements in upper extremity function using the combined robotic home exercise program intervention compared with home exercise program alone will be interpreted as evidence that supports the introduction of in‐home technology to augment the recovery of function poststroke.